2019
DOI: 10.1021/acs.molpharmaceut.9b00243
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine-Loaded Nanoparticles with Enhanced Tumor-Targeting Efficiency and Decreasing Toxicity: Developed by One-Step Molecular Imprinting Process

Abstract: Molecularly imprinted polymers have exhibited good performance as carriers on drug loading and sustained release. In this paper, vinblastine (VBL)-loaded polymeric nanoparticles (VBL–NPs) were prepared by a one-step molecular imprinting process, avoiding the waste and incomplete removal of the template, and evaluated as targeting carriers for VBL delivery after modification. Using acryloyl amino acid comonomers and disulfide cross-linkers, VBL–NPs were synthesized and then conjugated with poly­(ethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…The MIPs were loaded with a drug sensitive to high concentrations of glutathione (an environment that can be found in cancer cells), to target and treat tumors in vivo in mice [181]. Combining targeting folate-positive cancer cells with loading the MIPs with the glutathione-sensitive drug vinblastine showed that the drug accumulated in tumor tissues while the drug concentration decreased in organs, as compared with the pure drug, decreasing the toxicity of the drug to healthy tissues [182].…”
Section: Mips and Drug Deliverymentioning
confidence: 99%
“…The MIPs were loaded with a drug sensitive to high concentrations of glutathione (an environment that can be found in cancer cells), to target and treat tumors in vivo in mice [181]. Combining targeting folate-positive cancer cells with loading the MIPs with the glutathione-sensitive drug vinblastine showed that the drug accumulated in tumor tissues while the drug concentration decreased in organs, as compared with the pure drug, decreasing the toxicity of the drug to healthy tissues [182].…”
Section: Mips and Drug Deliverymentioning
confidence: 99%
“…Cancer cells use several mechanisms to bypass recognition by the immune cells, thereby escaping immune surveillance and progressing through metastases [4]. The cir-Appl.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MIPs with a lower degree of cross-linking are usually more advantageous for applications in drug delivery. Furthermore, the introduction of external materials such as thermosensitive polymers [70], magnetite [71] and specific moieties such as disulphide bonds [72] allows to MIPs to exhibit suitable changes in response to external stimuli, such as changes in pressure, pH, temperature, ionic strength, electric fields, chemicals and light.…”
Section: The Rationale Of Mips Used In Drug Deliverymentioning
confidence: 99%